Bullying Among Students in Bengkulu City : A Perspective from the Differential Association Theory - Ramdhan, Safira Wulansari; Rahmasari, Helda; Pradityo, Randy (Dinasti Research, 2026)
Violence such as bullying often occurs in the school environment, which should be a safe place to get protection. The number of bullying cases that occur among students has spread to all regions in Indonesia, including Bengkulu city. This shows that it is important to carry out comprehensive enforcement and that specific regulations are needed to prevent, protect, and resolve bullying. The problems in this study focused on the forms and characteristics of bullying behaviour that occurred and the factors that caused bullying by being analysed through differential association theory to be able to solve those problems by analysing it with the theory. This study uses a type of empirical research with the data sources used as primary data derived from interviews and questionnaires and secondary data in the form of literature studies. The results of the study found that the form of bullying that often occurs among students in Bengkulu City is verbal bullying with behavioural characteristics in the form of calling other students with abusive nicknames and being used as funny material, threatening and forcing someone, mocking and calling parents names. The factor that causes students to bully is because the family and environment have a negative impact on the character of students. In terms of differential association theory, these factors are in accordance with several propositions in theory, so students tend to study bullying behaviour from the surrounding environment.